Peningkatan Kualitas Masyarakat dalam Pencegahan Stunting pada Ibu-Ibu dan Remaja Perempuan Gunung Pasang, Desa Suci - Amilia, Winda; Pasaribu, Elen Bethania; Ar-Rafi, Muhammad Ghani; Maslahah; Wijaya, Natanael Okta; Aulia, Wilsa Dina; Pramitha P.A, Amanda; Hical W, Muhammad Irsyad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This community service activity aims to provide education on stunting and training on healthy food preparation for mothers in Gunung Pasang, Suci Village. The main objective of this activity is to enhance understanding and knowledge about stunting to break its cycle in Suci Village. The educational session was conducted on August 4, 2024, at the Gunung Pasang field, with 35 mothers and 10 teenage girls participating. The education included delivering materials related to stunting prevention. The results indicate a positive impact on the community, as evidenced by the increased knowledge of mothers and teenage girls, reflected in the pre-test and post-test results conducted by the health division of PPK Ormawa UKM-O Badminton. Similar counseling sessions are proposed to be held regularly to improve the quality of life of the residents, particularly the mothers and teenage girls